1995
DOI: 10.1063/1.468527
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the ethylene dimer from rotationally resolved near-infrared spectroscopy: A quadruple hydrogen bond

Abstract: Reported here are the first rotationally assigned near-infrared spectra of the ethylene dimer. The vibrational bands observed in this study correlate with ν9 and ν11 of the ethylene monomer, corresponding to C–H stretching motion. The spectral patterns have been identified as due to the vibrational transitions of a symmetric top molecule with D2d symmetry. This structure of the dimer has been predicted by ab initio calculations as the most stable geometry due to the fact that it enables the formation of four e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 40 publications
9
30
0
Order By: Relevance
“…Alberts et al [9] carried out ab initio calculations at the MP2 level, in which the D 2d cross form was not taken into account. Tsuzuki and Tanabe [11] calculated energies of a variety of dimer structures at the MP2/6-311G(2d, 2p) level and concluded that the D 2d structure is the most stable, in agreement with the results obtained by Ritter and Gruen [6], Chan et al [5], and Ahlrichs et al [7].…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Alberts et al [9] carried out ab initio calculations at the MP2 level, in which the D 2d cross form was not taken into account. Tsuzuki and Tanabe [11] calculated energies of a variety of dimer structures at the MP2/6-311G(2d, 2p) level and concluded that the D 2d structure is the most stable, in agreement with the results obtained by Ritter and Gruen [6], Chan et al [5], and Ahlrichs et al [7].…”
Section: Introductionsupporting
confidence: 77%
“…The equilibrium structure of the dimer is not the cross D 2d form reported in Refs. [5][6][7]11]. The energy difference between the global-minimum and cross forms is small (0.1 kJ mol -1 ) and thereby it is important to take into account large-amplitude motion involving deformations from the equilibrium structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented in Table 4 also demonstrate the change of all harmonic frequencies of ethylene molecules within the complex in comparison with harmonic frequencies of the ethylene monomer. It is of interest to compare the shifts observed in IR spectra for the frequencies of the ethylene dimer formed in a molecular beam [27,38,72] with the shifts of harmonic frequencies calculated in this work. In Ref.…”
Section: Theoretical Investigation Of the Ethylene Dimermentioning
confidence: 96%
“…The authors [25] have found the most stable configuration (D 2d ) of ethylene dimer, which agrees with the structure predicted from the analysis of infrared spectra of matrix isolated and solid ethylene [26] and of ethylene dimer formed in a molecular beam. [27] Afterward, Tsuzuki et al [28][29][30] have investigated the most stable configuration of C 2 H 4 -C 2 H 4 in more detail using the modern theoretical ab initio methods with larger basis sets including the complete basis set (CBS) limit. As a result of these investigations, the interaction energy of the most stable configuration of the ethylene dimer at MP2/CBS level of theory [30] is DE MP2 CBS (R e ) ¼ À1.54 kcal/ mol, which is 1.4 times larger then the interaction energy given in Ref.…”
Section: Introductionmentioning
confidence: 99%